DEVELOPMENT OF STAD-BASED STUDENT WORKSHEETS ON THE HUMAN RESPIRATORY SYSTEM FOR GRADE VIII STUDENTS - Mufliha, Zumrotul; Hayati, Nur (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2026)
The development of LKPD is expected to encourage students to actively participate through group work and better understand the human respiratory system.This study aims to develop Student Worksheets (LKPD) based on the cooperative learning model Student Teams Achievement Division (STAD) on the topic of the human respiratory system for eighth-grade students. The development model used is ADDIE, which includes five stages: analysis, design, development, implementation and evaluation. Validation results from experts indicate that the developed LKPD is highly valid, with an overall average score of 95.5%. The didactic aspect received a score of 97%, the construction aspect 96%, the technical aspect 95%, and the STAD-based cooperative LKPD characteristics 94%. These results suggest that the STAD-based LKPD is feasible for use as teaching material and can be further developed for other learning topics.